[P05] Perception and Acceptability of Open vs. Endovascular Treatment of Common Femoral Artery Disease: Barriers and Facilitators for Randomised Controlled Trials. (November 2022) - Kaneta, Gabriela; Saratzis, Athanasios; Zayed, Hany
Abstract : Objective: Endarterectomy remains the standard of care for common femoral artery (CFA) atherosclerotic disease; however, there have been advances in endovascular CFA therapies. Randomised controlled trials (RCTs) comparing CFA treatments have suffered from multiple pitfalls. This research assessed barriers and enablers of delivering high quality RCTs in this context from a healthcare professional's point of view. Methods: A mixed methods qualitative study was performed, including a structured online survey and face to face semi-structured interviews with healthcare professionals. Survey content and interview topic guides were developed following a literature review to identify ongoing and completed RCTs. Results were analysed using thematic analysis. Results: A total of 121 participants completed the online survey, including vascular surgeons (75, 62%) and interventional radiologists (22, 18%), mostly from the UK (92, 76%). A total of 61 participants (51%) were willing to take part in a RCT comparing open vs . endovascular CFA revascularisation. The majority (89, 74%) believed that such an RCT is urgently needed. Fifteen participants were interviewed face to face. Five main themes emerged regarding barriers and facilitators for a high quality RCT: factors directly limiting patient recruitment; clinicians' attitudes towards equipoise between treatments; clinicians' attitudes towards endovascular therapies; attitudes towards outcomes examined in a potential RCT; factors facilitating patient recruitment. Conclusion: The vast majority of those surveyed believed an RCT comparing CFA treatments is necessary and would not oppose taking part in it. Important barriers and enablers were identified, grouped in five overarching themes, which should be taken into consideration when designing and delivering such an RCT.